Pengaruh Nanokitosan-Ag/Cu pada Perkembangan Penyakit Antraknosa pada Cabai - Deden Dewantara Eris; Sri Wahyuni; Soekarno Mismana Putra; Ciptadi Achmad Yusup; Agustin Sri Mulyatni; Siswanto Siswanto; Eti Heni Krestini; Christina Winarti (Jurnal Ilmu Pertanian Indonesia, 2019)
Plant disease that often attacks the chili both in pre- and postharvest is fruit rot or commonly called with antracnose. Antracnose is caused by the attack of fungus Colletotrichum capsici. To control it, fungicides which are effective, safe for environmental and human are needed. For that purpose, people develop chitosanbased fungicide. Chitosan has been widely reported has an antimicrobial role for viral, bacterial, and fungal which can cause disease in plants. Further development of chitosan in order to increase antimicrobial activity is by the synthesis of Ag/Cu-Chitosan nanoparticles. Based on tests, it is known that both in the laboratory and greenhouse scale, Ag-ChNPs at a dose of 500 ppm and Cu-ChNPs at a dose of 1000 ppm have an inhibition effect on growth of Colletotrichum capsici by 17.3 and 42.3% meanwhile the treatment of Ag-ChNPs at a dose of 500 ppm and Cu-ChNPs at a dose of 1000 ppm were significantly potential in suppressing the incidence of the diseases on Tanjung, Ciko, and Kencana varieties of chili in greenhouse. Microscopically, the activities of antimicrobial compounds of Ag/Cu-Chitosan nanoparticles cause a damage to the fungal hyphae which is characterized by malformations that lead to the inhibition of hyphae growth. In the petri dish it was shown by the emergence of inhibition zone in the form of clear area around the treated disc paper.